STUDI PEMISAHAN BEBAN PENYULANG BARU SKTM GIS PANTAI INDAH KAPUK - Redaksi Tim Jurnal (Energi & Kelistrikan, 2017)
With increasing energy needs of electricity for industry and new customers in the crowded settlements, especially along the coastal areas of Beautiful Kapok, readiness and availability of resources to increase the burden of customers need efforts and appropriate measures. One of the most easy and safe to transmit electrical energy is by Splitting the load. The aim in this study is to determine the way and site selection as well as calculate the imposition of new penyulang. The distribution of electric energy from the parent booths toward the consumers can do with the distribution of direct or indirect distribution. Via Penyulang 20 kV distribution with the selected cable channels-free cable is a requirement of the disorder, in an effort to increase the quality of the distribution. In the system of electric power supply, voltage general conditions let it send penyulang allowed (5%-10%) according to the standard PLN. While according to ANSI standard C84, paragraph 1 is (4% and-10%) under normal conditions. The current that flows through the penyulang must not exceed the limit of the ability distribution against the denseness of the load. So that the required voltage quality is better. As for who should be taken into account in determining the location of the new building of the penyulang is based on the Division of the burden, then choose the type of cable that well that is kind of XLPE cable 240 mm2 aluminum as a necessary investment.